PENGEMBANGAN E-MODUL INTERAKTIF DENGAN PENDEKATAN PEMBELAJARAN MENDALAM PADA MATA PELAJARAN IPAS KELAS IV SD GUGUS III DI KECAMATAN BULELENG PADA MATERI PERUBAHAN WUJUD BENDA - Ni Putu Jesica Sapena Wardani; I Made Sedana; I Ketut Suparya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the limited use of interactive digital teaching materials in social studies learning which is still dominated by printed textbooks and lecture methods. This research aims to develop an Interactive E-Module with an in-depth learning approach to social studies subjects in grade IV elementary school material on changes in the form of objects in Cluster III of Buleleng District. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects in this study include instrument experts, media experts, material experts, linguists, teachers, and grade IV elementary school students. Data collection techniques were carried out through observation, interviews, and questionnaires. Data analysis used qualitative and quantitative descriptive methods. The results of the study showed that the Interactive E-Module developed obtained a very high level of validity with a media expert validity score of 0.98, a validity score of 0.93, and a linguist validity score of 0.96. These results show that the Interactive E-Module with an in-depth learning approach is suitable for use as a learning medium for science science class IV elementary school on material on the material of changing the shape of objects.